2019
DOI: 10.3168/jds.2018-15102
|View full text |Cite
|
Sign up to set email alerts
|

Development of a mathematical model to predict pool sizes and rates of digestion of 2 pools of digestible neutral detergent fiber and an undigested neutral detergent fiber fraction within various forages

Abstract: The digestion of neutral detergent fiber treated with amylase and sodium sulfite and ash corrected (aND-Fom) has been described as a single digestible pool and a fraction undigested in ruminants. Further, most models that predict rate and extent of digestion of aNDFom in the rumen assume first-order processes, in which the rates of digestion and passage are proportional to the pool size of aNDFom consumed and digested. Data exist demonstrating that the undigested fraction of aNDFom is not well described by a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
0
14
1
1
Order By: Relevance
“…The average ISpdRate, however, were lower in the current study (1.86%/h) than in that of Bender et al (2016), 1.9 to 2.8%/h (depending on the measurement method and regression model). In situ rates of pdNDFD observed in the current study were also lower compared with rates for corn silage NDF determined IS (Weisbjerg et al, 2007) or reported for an IV system by Raffrenato et al (2019). These discrepancies among studies are likely caused by different maturities of the corn silages and differences in the analytical methods used.…”
Section: Chemical Analyses and In Situ Degradabilitycontrasting
confidence: 85%
See 1 more Smart Citation
“…The average ISpdRate, however, were lower in the current study (1.86%/h) than in that of Bender et al (2016), 1.9 to 2.8%/h (depending on the measurement method and regression model). In situ rates of pdNDFD observed in the current study were also lower compared with rates for corn silage NDF determined IS (Weisbjerg et al, 2007) or reported for an IV system by Raffrenato et al (2019). These discrepancies among studies are likely caused by different maturities of the corn silages and differences in the analytical methods used.…”
Section: Chemical Analyses and In Situ Degradabilitycontrasting
confidence: 85%
“…The relationship between uNDF240 and NDFD30 makes sense, as fiber digestibility is expected to decrease with increasing lignification. Compared with IS NDFD, the lag time for NDFD in the traditional IV procedure (Goering and Van Soest, 1970), used for NIR NDFD30 calibration by LabB, appears to be short (1 to 3 h; Raffrenato et al, 2019) and would also contribute to the close relationship between NDFD30 and uNDF240. An examination of partial data for the 2017 and 2018 corn silage hybrids participating in PSUC-STP showed similarly high relationships between NIR uNDF240 and NDFD30 analyses (R 2 = 0.95, n = 107, and R 2 = 0.80, n = 127, respectively; data not shown).…”
mentioning
confidence: 99%
“…Undigested NDF for 30-, 120-, and 240-h time points for forage composite samples were analyzed using the Tilley-Terry rumen fermentation system (Raffrenato et al, 2019). Neutral detergent fiber with residual ash, using α-amylase and sodium sulfite (Van Soest et al, 1991), was determined by the Ankom A200 Fiber Analyzer filter bag technique (Ankom Technology Corp., Fairpoint, NY).…”
Section: Data Collection Sample Procedures and Analytical Methodsmentioning
confidence: 99%
“…T7, T9 and T10 treatments presented strong connection with FDA, as well as T5, T6 and T8 treatments that showed strong correlation with FDN. It´s known that such characteristics are undesirable for a quality forage because the fibers are one of the indigestible fractions to the rumen microbial fermentation (Raffrenato, et. al., 2019).…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%